2014
DOI: 10.1002/jbt.21551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Proliferation and Survival in Human Umbilical Cord Mesenchymal Stem Cells

Abstract: Cigarette smoking is known to have negative effects on tissue repair and healing. The aim of this study is to investigate the effects of nicotine in human umbilical cord mesenchymal stem cells (MSCs). After nicotine treatment, MSCs became pyknotic, vacuoles appeared in the cytoplasm and nucleus, and the nuclear boundary became fuzzy as observed using atomic force microscopy. Cell proliferation was inhibited in a dose-dependent manner (P < 0.05 for all concentrations). The proportion of apoptotic MSCs was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Exposure of short‐term cigarette smoke induced dysfunction to cell homing and cell survival of bone marrow‐derived mesenchymal stem cells . An in vitro study showed that exposure of human umbilical cord blood cells to 3–9 mM nicotine decreased cell proliferation in a dose dependent manner and increased apoptosis . In addition, an in vivo study showed that the proliferation capacity of mesenchymal stem cells isolated from chronic smokers was about 2.5‐fold less than that from non‐smokers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of short‐term cigarette smoke induced dysfunction to cell homing and cell survival of bone marrow‐derived mesenchymal stem cells . An in vitro study showed that exposure of human umbilical cord blood cells to 3–9 mM nicotine decreased cell proliferation in a dose dependent manner and increased apoptosis . In addition, an in vivo study showed that the proliferation capacity of mesenchymal stem cells isolated from chronic smokers was about 2.5‐fold less than that from non‐smokers .…”
Section: Discussionmentioning
confidence: 99%
“…26 An in vitro study showed that exposure of human umbilical cord blood cells to 3-9 mM nicotine decreased cell proliferation in a dose dependent manner and increased apoptosis. 27 In addition, an in vivo study showed that the proliferation capacity of mesenchymal stem cells isolated from chronic smokers was about 2.5-fold less than that from non-smokers. 28 These findings indicate that short-term or long-term exposure to cigarette smoke or its components can have cytotoxic effects on or reduce the proliferation rate of stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…This could be related to the decrease in Sox-9 expression during nicotine exposure and would be consistent with the impaired Sox-9 expression that we observed in smoking mothers. Several studies evaluated the effect of supplementing MSC cultures with various amounts of nicotine on MSC proliferation and chondrogenic differentiation [4345]. Concerning chondrogenic differentiation from adult MSC, two studies screening different specific markers of chondrogenesis only reported one (type II collagen or aggrecan) increased in the presence of various concentrations of nicotine [43, 44].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning chondrogenic differentiation from adult MSC, two studies screening different specific markers of chondrogenesis only reported one (type II collagen or aggrecan) increased in the presence of various concentrations of nicotine [43, 44]. Concerning proliferation, Ying et al showed that nicotine promotes BM-MSC proliferation [43] whereas Zeng et al reported decreased proliferation of MSC from the umbilical cord in the presence of nicotine in a dose-dependent manner [45]. These contradictory findings may result from experimental conditions as in vivo studies report long nicotine impregnation during pregnancy whereas in vitro studies report only occasional administrations.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, human umbilical cord blood cells exposed to 0.5–1.5 mg/ml nicotine (3–9 mM) showed dose‐dependent decreases in proliferation and increases in apoptosis ( p < .05 for all concentrations) . Significant decreases in proliferation have also been observed at concentrations as low as 0.1–10 µM ( p < .05) .…”
Section: Effect On Proliferationmentioning
confidence: 96%